Evaluation of open source software for mobile ad hoc routing in military tactical networks - Holmberg, Oscar (My University, 2014)
Evaluations of ad hoc routing protocols have been performed in several studies, both with hardware and in software simulators. However, the network topology plays an important role for the protocol performance. This master thesis evaluates OSPF, OLSR, Babel and Batman-adv in a tactical network set up. A tactical network is not a completely ad hoc scenario which makes it different from other studies. Furthermore, the protocols’ settings are varied and they are mainly tested against convergence time and generated overhead traffic. The aim is to find which routing protocol is most suitable in the tactical network scenario that is tested. The tactical network set up, consisting of 36 nodes, is created with virtual machines and software that emulates realistically radio links. The results show that OSPF can be configured to adapt to a tactical network. OSPF and Babel shows the best performance with respect to convergence time and generated overhead traffic. However, OLSR offers a lot of configuration possibilities which provides the potential to find a more suitable configuration than those that are used in the tests. Both Batman-adv and OLSR generates more overhead traffic than Babel and OSPF for the corresponding convergence time.
Keywords: Data- och informationsvetenskap; Computer and Information Science